Cambodia's Accession into the WTO - Kim Lydet (Graduate School of International Studies Ajou University, 2013)
This paper presents the importance of the World Trade Organization’s functions and principles to all country members as well as world economic growth due to values of the WTO: non-discrimination, transparency, predictability, dispute settlement, and multilateralism. Cambodia is regarded as a Least Developed Country, so globalization through bilateral agreements, multilateral agreements, and regional agreements are the best ways to promote national economic growth and reduce poverty. The WTO, therefore, is a vital gateway for Cambodia to exploit benefits by engaging itself to the huge world market. However, while there are benefits, there are challenges. The daunting tasks for the government were the deficiency of human and financial resources to fulfill the complex WTO requirements. The paper is divided into five chapters. Chapter 1 provides an overview of the thesis including literature review. Chapter 2 presents briefly the history, functions, and principles of the WTO. Chapter 3 shows the main reasons why Cambodia wanted to be a member and its expectations from membership. However, expectations and economic theories should be compatible. Some theories from famous economists – Adam Smith, David Ricardo, Eli Heckscher, Bertil Ohlin, Raymon Vernon, and Michael E. Porter – have been reviewed to see how international trade and globalization centuries ago work to generate world economic growth; then compare those theories with Cambodia’s situations. Chapter 4 discusses the main challenges – tariffs reduction and legislation reform – during application and after, and benefits from membership through technical assistances from other members and multi-donor trust funds for trade policy formulation, performing monitoring, as well as human capacity building. With the evidence of time series graphs, the effects of international trade on Cambodia are positive regarding GDP growth rate, GDP per capita, imports and exports, poverty reduction, foreign direct investment, and so on and so forth. Chapter 5 is conclusion on what has happened until now and what will happen in the future if Cambodia has done successfully some necessary reforms.
학위논문(석사)아주대학교 국제대학원 :국제통상학과,2013. 8
Keywords: International; Trade